The Royal Marsden manual of clinical nursing procedures : student edition - Dougherty, Lisa, ....-; Lister, Sara, ....-; West-Oram, Alexandra (red.), ....- (Chichester : Wiley Blackwell, 2015)
Managing the patient journey Assessment and discharge Infection prevention and control Supporting the patient with human functioning Communication Elimination Moving and positioning Nutrition, fluid balance, and blood transfusion Patient comfort and end of life care Respiratory care Supporting the patient through the diagnostic process Interpreting diagnostic tests Observations Supporting the patient through treatment Medicines management Perioperative care Vascular access devices : insertion and management Wound management